Efek Pemberian Seduhan Teh Hitam (Camellia sinensis L) Dan Cokelat (Theobroma cacao L) Terhadap Gambaran Histopatologis Hepar Rattus norvegicus - Damairia, Ema Rochayani; Sayekti, Fitria Diniah Janah (Jurnal Analis Kesehatan, 2022)
Black tea and chocolate are plants that contain caffeine. Chocolate is a commodity that generates foreign exchange for the country and is the main ingedient for making chocolate which also contains caffeine. Caffeine damages the liver by inhibiting the gowth of connective tissue in liver cells. The purpose of this study was to determine the histopathological effect on the liver organs of white rats given black and chocolate tea steeping and the damage that occurs when given in a predetermined dose and time. The research was conducted experimentally at the Anatomical Pathology Laboratory of the Sekolah Tinggi Ilmu Kesehatan Nasional. The study was divided into 7 treatment groups. Liver organs were observed macroscopically and microscopicallyfrom the results of histopathological preparations with Hematoxylin Eosin staining. The results of macroscopic observations there were no differences in the control and treatment goups. The results of microscopic observations in the black tea steeping goup 3 and 6 mg/200 g/day, and chocolate steeping 3, 6, and 12 mg/200 g/day there was degeneration, black tea steeped 12 mg/200 g/day there was necrosis. The results of the Mann Whitney test showed a significant difference in the black tea steeping goup at the three doses and 12 mg/200 g/day chocolate steeping, while 3 and 6 mg/200 g/day chocolate steeping did not show a significant difference. Based on the research, it can be seen